Research Trend in Korean Medicine Treatment for Hemifacial Spasm - Hyang Gi Lim; Eun Sil Heo; Sang Ha Woo; Jung Hee Lee; Jae Soo Kim; Seong Hun Choi; Hyun-Jong Lee (MEDrang Inc., 2023)
This study reviewed clinical papers reported on hemifacial spasm (HFS). Six online databases were searched for clinical papers published between January 2000 and December 2022. This study reviewed 14 studies, including 13 case reports and 1 combination of case reports and randomized controlled trials (RCTs). The most frequently used acupoints were ST7 and TE17, and the stomach meridian was the most frequently selected. Herbal medicine, pharmacopuncture, thread embedding acupuncture, cupping, moxibustion, and physical therapy were combined with acupuncture. The most frequently used evaluation method is Scott's scale. Out of 95 cases, 82 reported improved HFS symptoms after treatment. Our findings indicated the effectiveness of Korean Medicine treatment in treating HFS. However, evidence of efficacy and safety remains insufficient. Large-scale and well-designed investigations will be required in the future to corroborate these results. We believe that this paper will serve as the foundation for future RCTs.